2019
DOI: 10.3892/mmr.2019.10636
|View full text |Cite|
|
Sign up to set email alerts
|

lncRNA ROR promotes the progression of renal cell carcinoma through the miR‑206/VEGF axis

Abstract: Renal cell carcinoma (RCC) is the most common kidney malignancy, responsible for ~80% of all cases in adults. The pathogenesis of RCC is complex, involving alterations at both the genetic and epigenetic levels. Numerous signaling pathways, such as PI3K/Akt/mTOR and Wnt-β-catenin have been demonstrated to be associated with the tumorigenesis and development of RCC. Long non-coding RNAs (lncRNAs) are functional RNA molecules involved in the initiation and progression of cancer, and investigating the effects of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…Apoptosis of vascular cells contributes to the arterial architecture, especially when coordinated with matrix turnover and proliferation of vascular cells. Furthermore, studies have proven that ROR was also involved in vascular cell proliferation by regulating the expression of vascular endothelial growth factor (Shi et al, 2019). These results all indicate that ROR might be used as an agent to reverse vascular damage.…”
Section: Discussionmentioning
confidence: 82%
“…Apoptosis of vascular cells contributes to the arterial architecture, especially when coordinated with matrix turnover and proliferation of vascular cells. Furthermore, studies have proven that ROR was also involved in vascular cell proliferation by regulating the expression of vascular endothelial growth factor (Shi et al, 2019). These results all indicate that ROR might be used as an agent to reverse vascular damage.…”
Section: Discussionmentioning
confidence: 82%
“…The role of miR-206 in cancers is complicated and controversial. Decreased expression of miR-206 was found in rhabdomyosarcoma [ 26 ], lung cancer [ 28 ], ER + breast cancer [ 29 , 30 ], renal cell carcinoma [ 31 ], ER alpha + endometrioid adenocarcinoma [ 32 ], hepatocellular carcinoma [ 33 , 34 ] and glioma [ 35 ]. Upregulation of miR-206 inhibits the migration, invasion and proliferation of breast cancer [ 30 ], renal cell carcinoma [ 31 ], glioma [ 35 ], and head and neck squamous cell carcinoma [ 31 ], suggesting a tumor suppressor role of miR-206.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of miR-206 was found in rhabdomyosarcoma [ 26 ], lung cancer [ 28 ], ER + breast cancer [ 29 , 30 ], renal cell carcinoma [ 31 ], ER alpha + endometrioid adenocarcinoma [ 32 ], hepatocellular carcinoma [ 33 , 34 ] and glioma [ 35 ]. Upregulation of miR-206 inhibits the migration, invasion and proliferation of breast cancer [ 30 ], renal cell carcinoma [ 31 ], glioma [ 35 ], and head and neck squamous cell carcinoma [ 31 ], suggesting a tumor suppressor role of miR-206. Increased expression of miR-206 was found in breast cancer [ 30 , 36 ], esophageal carcinoma [ 37 ] and some soft tissue sarcomas [ 38 ], and high miR-206 expression was related to the poor prognosis of breast cancer [ 36 ] and esophageal carcinoma patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yang et al (28) found that the lncRNA TUG1 acted as a ceRNA of miR-196a to accelerate the proliferation, migration and invasion of RCC. Shi et al (29) demonstrated that the lncRNA ROR sponged miR-206 to promote RCC progression through increasing the protein expression level of VEGF. Furthermore, Xie et al (17) demonstrated that hsa_circ_0004771 facilitated the proliferation and inhibited apoptosis in breast cancer by functioning as a ceRNA of miR-653 to regulate the ZEB2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%